MENJADI BINTANG ATAU BINATANG Analisis Wacana “Othering” dalam Film “The Greatest Showman” - Devi Nirmala Muthia Sayekti (Sabda: Jurnal Kajian Kebudayaan, 2018)
This paper is aimed to analyse critically towards a film entitled “The Greatest Showman” related to its content which is problematic in its way to represent those “unique” persons. This film is created based on true story about P. T. Barnum, a politician and a business man in performing arts production. As a text in the cultural studies, this movie brings a discourse that can show how the reality is, especially in the field of entertainment and performing arts business. People considered as a “unique,” or maybe “weird,” always be narrated as the other, beyond the normal. They will be shown as an object to be laughed. From this point, I employed critical discourse analysis from Norman Fairclough, concerning in language used within this movie. We, then, would see how those “unique” persons will be placed as the other in very subtile way.